ILMU FORENSIK SEBAGAI LANGKAH PENYELESAIAN KASUS PIDANA MUTILASI DALAM PERANAN PEMBUKTIAN DI HADAPAN HUKUM - Karyn Karyn; Abdurrakhman Alhakim (Faculty of Law - Tarumanagara University, 2022)
Proof of murder and other crimes related to forensic science to reveal the perpetrators of crimes and their evidence, the purpose of this study was to determine the important role that forensic science has in solving crimes and the strength of the evidence of Visum et Repertum in court, the research method taken at This writing is a normative legal method in which Primary legal material contains premeditated murder as regulated in 340 of the Criminal Code, legislation Number 8 of 1981 concerning the Criminal Procedure Code, Number 29 of 2004 concerning Medical Practice, to solve this criminal case requires various types of knowledge. forensics, which is stated in the National Police Chief Number 10 of 2009 concerning Procedures and Requirements for Technical Requests for Criminal Cases at Case Incidents and Criminal Laboratory for State Evidence of the Republic of Indonesia. The case that was brought to the mutilation criminal case was focused on the decision Number 1036/Pid.B/2008/PN.DPK, the element of deliberate intentional killing of lives has been proven by fulfilling the implementation of Article 340 of the Criminal Code with this decision.Keywords: Criminal Acts, Forensic Science, Visum et Repertum, Premeditated murder